Corporate philanthropy and corporate financial performance: The roles of social response and political access - WANG, Heli (Institutional Knowledge at Singapore Management University, 2011)
Corporate philanthropy is expected to positively affect firm financial performance because it helps firms gain sociopolitical legitimacy, which enables them to elicit positive stakeholder responses and to gain political access. The positive philanthropy-performance relationship is stronger for firms with greater public visibility and for those with better past performance, as philanthropy by these firms gains more positive stakeholder responses. Firms that are not government-owned or politically well connected were shown to benefit more from philanthropy, as gaining political resources is more critical for such firms. Empirical analyses using data on Chinese firms listed on stock exchanges from 2001 to 2006 support these arguments.